Pengaruh Media Kartu Truth Or Dare Berbantuan Model Game – Based Learning Terhadap Hasil Belajar Pada Pembelajaran Pancasila Siswa Kelas III SDN Limbung Puteri - Nurfaida Mucthar; Lukman Ismail; Try Gustaf Said (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The problem formulation in this study is whether the truth or dare card media assisted by a game-based learning model has an effect on learning outcomes in Pancasila learning for third-grade students of SDN Limbung Puteri. The purpose of this study is to determine the effect of truth or dare card media assisted by a game-based learning model on learning outcomes in Pancasila learning for third-grade students of SDN Limbung Puteri. This study uses a quantitative approach with an experimental research type. The results of the study showed a significant difference between the experimental class and the control class in achieving learning outcomes. In the experimental class, the average posttest score reached 96.48, while in the control class it was only 72.96. Based on these results, it can be concluded that the application of Truth or Dare Card Media Assisted by a Game-Based Learning Model can improve the learning outcomes of third-grade students of SDN Limbung Puteri.